Optimalisasi Perkembangan Kognitif Anak Usia Dini melalui Bimbingan Penggunaan Game Edukasi Digital di TK Barunawati Ampenan - Putri, Dinda Riris Nurviana; Gunawan, Gunawan; Astini, Baik Nilawati (Indonesian Journal of Education and Community Services, 2023)
Cognitive development in early childhood is a crucial foundation for future learning success. In the digital era, following the challenges of the pandemic, the use of digital educational media has become highly relevant, yet it requires proper guidance for optimal results. This community service activity aimed to optimize the cognitive development of children aged 5-6 years at TK Barunawati Ampenan through guided use of digital educational games, specifically "Stickman Party." The implementation method involved training and direct assistance for teachers and children in utilizing the game. The results indicate that structured guidance effectively enhanced children's focus, concentration, creativity, and problem-solving abilities. Teachers and parents also demonstrated improved understanding and skills in facilitating digital learning, thereby creating a more interactive and effective learning environment. This optimization contributes to engaging and meaningful learning experiences for early childhood.